Personality and Mental Well-Being of Adolescent Students from Dysfunctional Families: Basis for the Development of an Intervention Program - Kisse, Limar T. (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2025)
The family structure, including parents, marriage and children, is said to be the building block of society and the most basic form of social organisation, and so it should be a place where children grow up in good mental and physical health (although reality is often somewhat different). In dysfunctional families, young people may experience emotional suffering or instability and may not receive regular support from their family, which can affect their psychological development and future development. This research analyzed the association of personality traits with the mental health of adolescents from dysfunctional families in a quantitative manner based on personality traits and well-being levels, demonstrating a characteristic profile of high openness and agreeableness combined with relatively low conscientiousness, extraversion, and neuroticism. Of these, characteristics such as conscientiousness emerged as a robust predictor of mental well-being, suggesting that structure, self-control and goal directed behaviour may be particularly important to individuals’ resilience in the face of challenging family environments. The results bear on the possibility that developing conscientious habits may make adolescents more resistant to life’s tribulations and provide them greater equanimity. For these reasons, preventive interventions that involve parents and teachers and students themselves, and promote resilience, re-oriente coping strategies and positive parenting are advisable. Such interventions contribute not only to better family communication and mutual understanding, but to greater mental health among adolescents under difficult circumstances